DISKURSUS DEMOKRASI DELIBERATIF DI INDONESIA - Muzaqqi, Fahrul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
The discourse of deliberative democracy in Indonesia has become the serious debate after New Order in Indonesia. This debate is motivated by the need to find a form of democracy that are relevant to Indonesian society. This study used qualitative methods and focused to analyze the theory of deliberative democracy, confirming the view of experts. Further mapping the influence delibratif democracy in Indonesia. The findings of this study indicate an opportunity for deliberative democracy into the spirit, even has been applied in Indonesia. The spirit of democracy in Indonesia lies in the spirit, also known as consensus. The discourse of deliberative democracy in Indonesia is very popularized by Habermasian style of deliberative model which includes various dimensions of life, namely the political, cultural, social, legal, economic and other dimensions.